Reducing the risk of rostral bending failure in Curculio Linnaeus, 1758. (May 2021) - Jansen, M. Andrew; Niverty, Sridhar; Chawla, Nikhilesh; Franz, Nico M.
Graphical abstract: Abstract: With over 300 species worldwide, the genus Curculio Linnaeus, 1758 is a widespread, morphologically diverse lineage of weevils that mainly parasitize nuts. Females use the rostrum, an elongate cuticular extension of the head, to excavate oviposition sites. This process causes extreme bending and deformation of the rostrum, without apparent harm to the structure. The cuticle of the rostral apex exhibits substantial modifications to its composite structure that enhance the elasticity and resiliency of this structure. Here we develop finite element models of the head and rostrum for three Curculio species representing disparate North American clades and rostral morphotypes. The models were subjected to varying apical loads and to prescribed dislocation of the head capsule, with and without representing the cuticular modifications of the rostral apex. We found that the altered layer thicknesses and macrofiber orientation angles of the rostral apex fully explain the observed elasticity of the rostrum. These modifications have a synergistic effect that greatly enhances the flexibility of the rostral apex. Consequently, the cuticle composite profile of the rostral apex substantially mitigates the risk of fracture in dorso-apical flexion. Removing the cuticular modifications, in turn, causes a negative margin of safety for rostral bending, implying strong risk of catastrophic structural failure. The occipital sulci were identified as an important source of biomechanical constraint upon the elasticity of the rostrum, and exhibit the greatest risk of failure within this structure. The apical cuticle profile greatly reduced the maximum stresses and strain energy accumulated in the rostrum, thereby resulting in a positive margin of safety and reducing the risk of fracture. Our findings imply that the primary selective pressure influencing the evolution of the rostral cuticle was most likely negative selection of structural failure caused by bending. Statement of significance: Weevils are among the most diverse and evolutionarily successful animal lineages on Earth. Their success is driven in part by a structure called the rostrum, which gives weevil heads a characteristic "snout-like" appearance. Nut weevils in the genus Curculio use the rostrum to drill holes into developing fruits and nuts, into which they deposit their eggs. During oviposition this exceedingly slender structure is bent into a straightened configuration – in some species up to 90 ∘ – but does not suffer any damage during this process. Using finite element models of the rostra of three morphologically distinct species, we show that the Curculio rostrum is only able to withstand repeated, extreme bending because of modifications to the composite structure of the cuticle in the rostral apex. These modifications were shown previously to enhance the intrinsic toughness of the cuticle; in this study, we demonstrate that modification of the rostral cuticle also results in more evenly distributed bending stresses, further reducing the risk of fracture. This is the first time that the laminate profile, orthotropic behavior, and functional gradation of the cuticle have been incorporated into a three-dimensional finite element model of an insect cuticular structure. Our models highlight the significance of biomechanical constraint – i.e., avoidance of catastrophic structural failure – on the evolution of insect morphology.